Creative Pedagogies for English Mastery: Drama, Games, and Simulation Unleashed - Doppalapudi, Rajani (Journal of Neonatal Surgery, 2025)
Modern English language and literature education is shifting toward student-centered, experience-rich environments. Traditional lecture-based instruction fails to provide the engagement and immersion necessary for deep language acquisition and literary analysis. This research paper examines the integration of activity-based learning (ABL) strategies—specifically drama, role play, simulations, and gamification—in enhancing English language and literature learning. Drawing from constructivist and experiential learning theories, this paper outlines the efficacy of these methods across vocabulary, grammar, reading, speaking, and interpretation skills. Through case studies, theoretical models, and validated pedagogical practices, we demonstrate how activity-based strategies transform passive learners into active language users. The work concludes with visual diagrams, sample tools, and appendices for classroom adaptation, ensuring broad applicability across varied learner levels.